(untitled) (Vietnam Journal of Community Medicine, 2026)
The Central and Central Highlands regions have high prevalence rates of several helminth infections, in addition to soil-transmitted helminths (STH), several parasitic diseases transmitted from animals to humans such as fascioliasis, Opisthorchiidae spp., and Taenia saginata, have been recorded in many localities in the region. Therefore a comprehensive investigation was conducted to determine the prevalence of helminths infection in communities at some selected high-risk locations. Objective: To determine the prevalence and intensity of infection with selected helminth species in humans at the research locations using the Kato - Kazt stool examination technique. Research methods: A descriptive cross-sectional study. Results: The overall prevalence of helminth infections was 44.31% in Dak Mon, 27.14% in Dak Kroong, 8.45% in Dak Buk So, and 5.45% in Quang Tam. The mean infection intensity of soil-transmitted helminths was 47.46 eggs per gram (EPG) for Ancylostoma duodenale/Necator americanus (Dak Glei district: 79.4; Tuy Duc district: 12.08), 1.50 EPG for Trichuris trichiura (1.90; 1.01), and 1.13 EPG for Ascaris lumbricoides (1.50; 0.71). The mean intensity of Opisthorchiidae spp. was 171.76 EPG in Dak Mon, 23.38 EPG in Dak Kroong, and 3.1 EPG in Dak Buk So. Conclusion: The prevalence and intensity of several helminth infections were identified among communities in Dak Mon and Dak Kroong communes (Dak Glei district) and Dak Buk So and Quang Tam communes (Tuy Duc District).